The Effect of Radixin on the Function and Expression of Organic Anion Transporting Polypeptide 1B1 - Chunxu Ni; Longxia Tang; Xuyang Wang; Zichong Li; Mei Hong (Biology, 2025)
Organic anion transporting polypeptide 1B1 (OATP1B1) is selectively expressed at the basolateral membrane of human hepatocytes and plays a crucial role in the absorption of various xenobiotic compounds, including many important clinical drugs. Oligomerization with regulatory proteins is a common mechanism for regulating membrane protein functions. In the present study, we found that knocking down the scaffold protein radixin, which is the major member of the ERM family expressed in the liver, significantly enhanced the uptake function of OATP1B1. On the other hand, the overexpression of the phospho-mimic form of radixin (radixin-D) reduced the uptake function and cell surface level of OATP1B1, while the wild-type and phospho-dormant form of radixin (radixin-A) did not exhibit the same effect. Further investigation revealed that radixin interacts with OATP1B1. Activation of protein kinase C (PKC), which our previous study showed accelerates the internalization of OATP1B1, was found to increase the phosphorylation level of radixin associated with OATP1B1. The knockdown of radixin significantly diminished the suppressive effect of PKC on the function and cell surface levels of OATP1B1. These results suggested that OATP1B1 forms complexes with radixin, which may be phosphorylated by PKC, leading to reduced cell surface expression and activity of the transporter.